Hubungan Pengetahuan dan Sikap Ibu Dengan Kejadian ISPA Pada Anak di Puskesmas Padang Bulan Medan - Mawati Manalu; Vina Yolanda Sari Sigalingging; Lindawati Farida Tampubolon (Lembaga Pengembangan Kinerja Dosen, 2024)
ARI (upper respiratory tract infection) in children that is not treated quickly will result in difficulty breathing, difficulty drinking, seizures and even decreased consciousness and even death. This research aims to determine the relationship between mother's knowledge and attitudes and the incidence of ARI in children at the Padang Bulan Health Center, Medan. The type of research is correlation with a cross-sectional design. Respondents are mothers who took their children for treatment to the Community Health Center, totaling 72 people and are taken using accidental sampling techniques. The research instrument used questionnaire. The research results show that of the 10 respondents who have less knowledge, all experienced ISPA. Of the 28 respondents who have sufficient knowledge, the majority experienced ISPA are 34.7% and only 4.2% do not experience ISPA. Of the 34 well-informed respondents, the majority experienced ARI, 36.1%, and only 11.1% do not experience ARI. The statistical test results show a P value = 0.046 with a correlation coefficient value of -0.236. Thus, it can be concluded that maternal knowledge is related to the incidence of ARI, where the strength of this relationship is weak and has a negative pattern, meaning that mothers with good knowledge do not guarantee that their children are free from ARI.